Information Structure Within Interfaces Consequences for the Phrase Structure - Gürer, Asli (Interface Explorations [IE] ;, 2020)
The realization of information structural units has been intriguing as information packaging has reflections in the semantic, pragmatic, syntactic and prosodic domains. This book extends the investigation by bringing data from all these domains and presenting an analysis for the model of grammar.Based on three-way classification for information packaging, semantic investigation presents insights on compositionality and positional restrictions for topic, focus and discourse anaphoric phrases. The prosodic experimental studies reveal how focus shapes prosody and how diverse languages encode such information packaging. Drawing on the findings of experimental studies reflecting the interaction of information structure with quantifier scope, negation and aspectual markers,clause internal functional projections and scope domains are proposed in the syntactic analysis. The analysis offers new perspectives for movement operations, functional categories, phases which are central themes for the Minimalist Program.Building on the investigation of information structure within semantic, prosodic, syntactic perspectives, the book will appeal to researchers working on either of these domains or their interfaces.